The students’ acceptance of learning management systems in Saudi Arabian Universities - Mutasem K. Alsmadi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
For distance learners, continuous official education is very important for improving knowledge and learning experience in order to meet the career challenges in the modern world. This work studies the success factors which affect the use of LMS and evaluates the ability to apply the proposed model in the field of distance learning (DL) particularly in higher education. The survey was carried out on higher education learners who were included in the DL instructions. This work has utilized a questionnaire that was modified from literature to inspect three measurements, system design, system usage, and system outcome. Utilizing the obtained survey data for students of DL (N=149), the path analysis discovered that the design of the system has a significant effect on the satisfaction of users and intention for using LMS which affects the use of the system. Consequently, the satisfaction of users and the system used has a great impact on the net benefit.